Effect of pH on nitrous oxide production and emissions from a partial nitritation reactor under oxygen-limited conditions. Issue 6 (June 2016) - Lv, Yongtao; Ju, Kai; Wang, Lei; Chen, Xiaoqiang; Miao, Rui; Zhang, Xueling
Graphical abstract: Highlights: In a PN reactor, N2 O emissions decreased with the increase in initial pH. N2 O production inside sludge aggregates were quantified by using microelectrodes. A decrease in pH led to increased N2 O emissions from denitrification. Abstract: The effect of pH on nitrous oxide (N2 O) emissions from a laboratory-scale partial nitritation sequencing batch reactor under oxygen-limited conditions was investigated from both macro- and microscopic viewpoints. During the aeration period of a single cycle, N2 O emissions decreased when the initial pH increased from 7.5 to 8.5. By application of microelectrodes, N2 O production was observed inside entire sludge aggregates, and it increased with decreasing pH from 8.5 to 7.0. At pH 8.0 and 8.5, N2 O was mainly produced in the outer layer (<1000 μm) of sludge aggregates, where nitritation mainly occurred. At pH 7.0 and 7.5, N2 O production was mainly observed in the inner layer (>1000 μm), where the dissolved oxygen was almost depleted, revealing that the dominant pathway here was denitrification. Under oxygen-limited conditions, a decrease in pH led to increased N2 O emissions from denitrification pathway.